Therapeutic monitoring of amiodarone and desethylamiodarone after surgical ablation of atrial fibrillation-evaluation of the relationship between clinical effect and the serum concentration - Hrudikova, Erika; Grundmann, Milan; Kolek, Martin; Urinovska, Romana; Kacirova, Ivana (Saudi pharmaceutical journal, 2021)
BACKGROUND: Association between clinical effect and serum concentration of amiodarone (AMI) and its active metabolite desethylamidarone (DEA) in patients after surgical ablation (SA) of atrial fibrillation (AF) has not yet been studied. AIMS: We wanted to find a correlation between AMI and DEA serum concentration and maintaining sinus rhythm (SR) after SA of AF. METHODS: Sixty eight patients with AF who had undergone surgical ablation between 2014 and 2017 were included in a single-centre, prospective, observational study. Maintaining of SR was evaluated by standard 12-lead ECG and 24-hour Holter ECG monitoring at months 1, 3, 6 and 12 following surgery. Therapeutic monitoring of AMI and DEA concentrations was done to optimize therapy and adverse effects were followed up. RESULTS: We have noticed a high success rate in maintaining of SR (overall 83%). The median of serum concentration of AMI was 0.81 mg/L (range 0.16-2.35 mg/L) and DEA 0.70 mg/l (range 0.19-2.63 mg/L). No significant differences were found in the serum concentratration of AMI, DEA or DEA/AMI concentratration ratios between patients with SR and persistent supraventricular tachyarrhythmia except on the second outpatient visit. We observed significant correlation between serum concentration of DEA and thyroid-stimulating hormone elevation. CONCLUSION: We confirmed the efficacy of AMI and DEA at the measured serum concentrations. However, analysis of these concentrations alone cannot replace assessment of the clinical response for treatment. Establishment of individual AMI (and DEA) concentrations at which the optimal therapeutic response is achieved seems to be advantageous. Therapeutic monitoring of AMI and DEA is helpful in personalised pharmacotherapy after SA of AF.
Keywords: AF, atrial fibrillation; Amiodarone; Desethylamiodarone; AMI, amiodarone; ECG, electrocardiogram; TSH, thyroid-stimulating hormone; ST, supraventricular tachyarrhythmia; Serum concentration; SR, sinus rhythm; GMT, gama glutamyl transferase; Maze procedure; ALT, alanine transaminase; Sinus rhythm; CABG, coronary artery bypass graft; TDM, therapeutic drug monitoring; DEA, desethylamiodarone; AST, aspartate transaminase; SA, surgical ablation; Atrial fibrillation